SURGICAL MANAGEMENT OF COMPLICATED FOREIGN BODY SYNDROME IN SHE-BUFFALO A CASE REPORT - Dahimwal, Dinesh; Singh, Rammehar; Pal, Madan; Choudhary, RN; Potliya, Sandip (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Recurrent rumen tympany is common disease of fore stomach like foreign body syndrome, diaphragmatic hernia and traumatic reticulitisand resulted inheavy economic losses due to sharp drop in milk yield and cost of treatment (Schweizer et al., 2005).Functional reticulo-omasal and pyloric stenosis,trichobezoars and phytobezoars, liver abscess and enlarged mediastinal lymph nodes pressing the oesophagous have also been observed to cause recurrent tympany in bovine. For temporary relief from tympany there are several invasive and non-invasive methods. The most common practice is to insert a trocar and cannula or a 6-8 inches long 16 G hypodermic needle in the rumen through left para-lumbar fossa. The non-invasive methods include giving the antibloat preparations per orally. Sometimes at field level the vets and paravets perform irrationally to relieve tympany which leads to occurance of such cases